1996
DOI: 10.1093/ageing/25.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Gait Disturbance in Alzheimer's Disease: A Clinical Study

Abstract: Gait disturbance is common in patients with Alzheimer's disease (AD). The aim of this study was to analyse the clinical gait syndromes of patients with AD using Nutt's classification. Fifty-five patients who satisfied the NINCDS-ADRDA criteria for probable AD and 55 controls were recruited from a geriatric and a psychogeriatric unit. Patients with classical musculoskeletal or neurological syndromes causing gait disturbance were excluded. A standardized neurological examination was carried out in all subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
1
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(92 citation statements)
references
References 19 publications
10
74
1
7
Order By: Relevance
“…Such difference was found only in the moderate stage of the disease. The same results were described by O'Keeffe et al 25 in an analysis of balance and gait in AD through the Tinetti test, where they encountered dysfunction in balance in 36% of controls, 43% of mild AD, 60% of moderate AD, and 79% of severe AD. In our study, the fallers group achieved lower (although not statistically different) scores in the BBS, except for the moderate AD patients.…”
Section: Discussionsupporting
confidence: 81%
“…Such difference was found only in the moderate stage of the disease. The same results were described by O'Keeffe et al 25 in an analysis of balance and gait in AD through the Tinetti test, where they encountered dysfunction in balance in 36% of controls, 43% of mild AD, 60% of moderate AD, and 79% of severe AD. In our study, the fallers group achieved lower (although not statistically different) scores in the BBS, except for the moderate AD patients.…”
Section: Discussionsupporting
confidence: 81%
“…Frontal release signs, impaired gait, and increased rigidity may occur more frequently early in the course of dementia. 31,[61][62][63][64][65] In a recent study, gait disturbance was often reported to the family doctor up to five years before dementia was diagnosed. 65 While risk factors for AD in the general population are of interest, it is unclear whether they are relevant in predicting dementia in that subset of the population presenting to a Memory Clinic with mild cognitive impairment.…”
Section: Clinical Risk Factors For Development Of Dementia and Admentioning
confidence: 99%
“…Previous studies suggested that impaired balance performance is more evident in AD individuals when compared with controls 10 and declines according to the dementia stage 11 . Similar results were reported by KatoNarita et al 12 when the Berg Balance Scale (BBS) was employed to measure balance performance in mild and moderate AD.…”
mentioning
confidence: 95%